IMPLEMENTATION AND COMPARISON OF SERVICE LEARNING PEDAGOGY IN A SUBJECT OF INTERIOR DESIGN - Santosa, Adi (Dimensi Interior, 2007)
Referring to the case study in the Department of Interior Design of Petra, the implementation of service learning pedagogy in a subject of design can give additional values for students. Considering aspects of psychology, social, economy, and culture, students can solve the real problems in their society. Compared to two standard systems of approach in pedagogy: teacher-centred approach and learner-centred approach, it is known that implementation of service learning in the subject of Interior Design II is compatible with both of them. The implementation of service learning is conducive for students to develop all of their potencies of domains: cognitive, affective, psychomotor; and factors of education: cognitive and metacognitive, motivational and affective, developmental and social, individual differences. Abstract in Bahasa Indonesia : Gereja Katolik memiliki peraturan-peraturan dan makna-makna tertentu, Budaya Jawa pun memiliki aturan, batasan, serta makna tersendiri baik dalam tatanan bangunan yang meliputi elemen pembentuk ruang, fasilitas, maupun pendukung lainnya. Sedangkan dalam inkulturasi kedua budaya yang saling berhubungan ini harus berjalan seiring. Oleh karena itu, akan dibandingkan kedua budaya tersebut untuk mengetahui sejauh mana kesesuaian makna yang dapat dicapai apabila terjadi inkulturasi Budaya Jawa dengan Gereja Katolik. Dari hasil perbandingan tersebut diketahui bahwa wujud fisik Budaya Jawa sebagai unsur inkulturasi interior Gereja Katolik tidak semuanya dapat diterapkan karena tidak adanya kesesuaian makna dan hubungan timbal balik antara keduanya. Wujud Budaya Jawa yang dapat dijadikan unsur inkulturasi dalam interior Gereja Katolik antara lain zoning, elemen pembentuk ruang lantai dan plafon, warna, tata letak bangku umat dan perabot untuk pemimpin. Kata kunci: Interior Gereja Katolik, Liturgi, Inkulturasi Budaya, Budaya Jawa